Heat storage and release characteristics of composite phase change wall under different intermittent heating conditions. (16th March 2019) - Li, Yanru; Long, Enshen; Jin, Zhenghao; Li, Jin; Meng, Xi; Zhou, Jing; Xu, Luting; Xiao, Dongtian
Abstract : During intermittent heating, the heat storage and release of building envelopes are caused by indoor thermal environment variations. The heat storage and release process of the building envelope inside can be used to reduce heat loss in intermittent cycles and maintain the indoor thermal environment for occupant comfort while saving energy by efficiency in the operation. In this research, the building envelope was integrated with phase change materials, and the heat transfer model was established and verified to analyze the heat storage and release processes of composite phase change wall (composite-PCW) under two typical intermittent heating conditions. Effective heat storage utilization rate η and heat loss rate ε were used to evaluate the wall's heat storage and release characteristics and energy efficiency, and the composite-PCW was compared with a solid brick wall. The results show that (1) the η of the composite-PCW was 75.07% in the long intermittent condition; (2) the thermal processes were relatively stable in the last three cycles of the short intermittent condition, and the η was greater than 70%; and (3) the ε of the composite-PCW was smaller under the two intermittent conditions compared with the solid brick wall and was reduced by more than 36%.